HEMT Noise Modeling for D Band Low Noise Amplifier Design - Ao Zhang; Jianjun Gao (IEEE Journal of the Electron Devices Society)
An improved EEHEMT nonlinear model with noise model has been developed in this paper. Empirical formulas of bias dependent noise model parameters are given. A four-stage 120–160 GHz monolithic low-noise amplifier (LNA) fabricated with the 70nm InAlAs/InGaAs/InP HEMT technology. The simulated results of S-parameters and noise figure show the good agreement with measured data to verify the accuracy of the proposed model.